An Analysis of Cyclone Disaster Management in Gangetic West Bengal from 2001 to 2020 - Monalisa Maity (Mathematical Statistician and Engineering Applications, 2022)
Cyclonic storms and depressions that impact West Bengal develop and strengthen over the Bay of Bengal, primarily between the months of May and November. Typically, their movement direction is towards the west-northwest as they make their way over the coastline. Storms and depressions lose strength when they move onto land. Therefore, due to its location on the eastern coast of India, the state frequently endures the intense force of severe storms and depressions originating from the Bay of Bengal. Tropical cyclones (TCs) which are accompanied by very heavy to extremely heavy rain, gales and storm surges are the most devastating phenomena among all natural disasters. The extensive coastal belts of India are exposed to TCs, which originate in the North Indian Ocean (NIO) including the Bay of Bengal and the Arabian Sea every year. Cyclone warning is one of the most important functions of the India Meteorological Department and it was the first service undertaken by the Department as early as in 1865. Disaster management plays a significant role in combating cyclones. The objective of disaster management activities is to exert authority over catastrophe and emergency circumstances and establish a framework for assisting individuals in danger to prevent or recuperate from the consequences of the disaster. This paper reflects an analysis of Cyclone Disaster Management in Gangetic West Bengal from 2001 to 2020.